Web-Based Task Organizer for Enhanced Productivity - Anika Kirana Venkat; Chiranjeev Mishra; Sameera P; Keerti Kulkarni (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Web-Based Task Organizer for Enhanced Productivity (WBTO) mainly aims to improve task management and overall increase in productivity. In our system we offer features such as task prioritization, categorization, due dates and recurrence options which is integrated into a user friendly interface. We use a full stack approach using java for the back end logic, JavaScript for a dynamic user interface and a SQL database for preserving data storage. It provides key features like task creation, categorization, prioritization, scheduling and progress tracking and interactive functionalities and ensuring data integrity and privacy. As this not only improves individual productivity but also further provides group work collaboration allowing for much faster task tracking, reminders and analytics which improves overall user experience.